2019
DOI: 10.1101/600981
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Icosahedral viruses defined by their positively charged domains: a signature for viral identity and capsid assembly strategy

Abstract: Capsid proteins often present a positively charged arginine-rich region at the N and/or C-termini that for some icosahedral viruses has a fundamental role in genome packaging and particle stability. These sequences show little to no conservation at the amino-acid level and are structurally dynamic so that they cannot be easily detected by common sequence or structure comparison. As a result, the occurrence and distribution of positively charged protein domain across the viral and the overall protein universe a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, the N-terminal domain of flavivirus capsids, unresolvable by crystallography, is flexible and also highly positively charged. Disordered, basic peptide tails are highly common in nucleic-acid binding proteins with roles in RNA or DNA compaction or packaging such as the lysine-rich eukaryotic histone tails [50] or arginine-rich motifs in viral capsid proteins from icosahedral non-enveloped viruses [51]. Similarly, in flavivirus capsid, the disordered basic tail is implicated in the packaging of viral genome.…”
Section: Structure Of Flavivirus Capsid and Its Role In Packagingmentioning
confidence: 99%
“…However, the N-terminal domain of flavivirus capsids, unresolvable by crystallography, is flexible and also highly positively charged. Disordered, basic peptide tails are highly common in nucleic-acid binding proteins with roles in RNA or DNA compaction or packaging such as the lysine-rich eukaryotic histone tails [50] or arginine-rich motifs in viral capsid proteins from icosahedral non-enveloped viruses [51]. Similarly, in flavivirus capsid, the disordered basic tail is implicated in the packaging of viral genome.…”
Section: Structure Of Flavivirus Capsid and Its Role In Packagingmentioning
confidence: 99%
“…The presence of a disordered, positively charged region on the N-terminus of C protein is reasonable since numerous other nucleic acid binding proteins also contain disordered, positive peptide regions. Two examples are the lysine-rich regions of eukaryotic histones and the arginine-rich capsid regions of non-enveloped icosahedral viruses such as the human astrovirus ( Erler et al, 2014 ; Krishna, 2005 ; Requiao et al, 2019 ). An alanine scanning mutagenesis study from Samsa et al (2012) demonstrated that efficient DENV virus production relied specifically on the conservation of the basic regions in the N-terminus of C, and not the conservation of specific amino acids.…”
Section: Flavivirus Structural Proteins: Structure and Functionmentioning
confidence: 99%